Identification of Three Families Carrying Hb Anti-Lepore Hong Kong Variant in Guangxi, China, and Analysis of Their Hematological Data. (2nd November 2022) - Long, Ju; Gong, Feifei; Sun, Lei; Lai, Guangping; Chen, Lihua; Peng, Mingkui; Yu, Chunhui; Liu, Enqi
Abstract: Thalassemia is a single-gene genetic disease with a high incidence in southern China. To prevent and control thalassemia, the most commonly used procedure is hematology testing and hemoglobin (Hb) analysis, followed by thalassemia gene analysis in positive individuals. During routine testing for thalassemia, we identified three individuals with Hb A2 levels of >10.0%. The results of conventional thalassemia gene analysis of these individuals cannot explain this feature, and there is a possibility of carrying novel thalassemia gene variants. Therefore, we collected samples from these three families for further analysis of the thalassemia gene. The research team used multiplex ligation-dependent probe amplification (MLPA) to analyze the three families, and the analysis results showed that their molecular biological characteristics were similar to those of Hb Anti-Lepore Hong Kong (NG_000007.3: g.63210_70621dup). Then, gap-polymerase chain reaction (gap-PCR) and sequencing methods were used for verification, and it was confirmed that the variant carried by these three families was indeed Hb Anti-Lepore Hong Kong. Three individuals carrying both the – – SEA (Southeast Asian) and Hb Anti-Lepore Hong Kong variants were also detected in this study, and these individuals had slightly lower Hb A2 results than those carrying Hb Anti-Lepore Hong Kong alone. Further analyses revealed that the carrier rate of this variant is about 0.03% in the population, thus identifying it as a rare variant.